14 Radial artery access for primary percutaneous coronary intervention is associated with reduced bleeding and mortality. (27th November 2017) - Krishnamurthy, Arvindra; Keeble, Claire; Somers, Kathryn; Burton-Wood, Natalie; Anderson, Michelle; Harland, Charlotte; McLenachan, James M; Blaxill, Jonathan M; Malkin, Christopher J; Blackman, Daniel J; Wheatcroft, Stephen B; Greenwood, John P
Abstract : Introduction: We assessed the association of arterial access site with clinical outcomes following PPCI in a large consecutive patient-series. Methods: Demographic, clinical, and 30 day follow up data for all patients undergoing PPCI between 1–1–2009 and 31–12–2011, and 1–1–2013 and 31–12–2013, in Leeds General Infirmary, were collected prospectively. All arterial access sites were recorded. Cross-overs were analysed by initial arterial access site. Patients presenting with cardiogenic shock and/or cardiac arrest were excluded. Clinical endpoints were 30 day MACE (total mortality and major bleeding. Multivariable analysis was performed with Cox proportional hazards models adjusting for major cardiovascular risk factors. Results: 4056 patients underwent PPCI during this period (464 excluded due to cardiogenic shock and/or cardiac arrest). Data for 30 day bleeding and MACE were available for 3381 (94.2%) patients. 111 patients crossed over from radial to femoral access, and 102 patients crossed over from femoral to radial access. Transradial (n=2389; 70.7%) PPCI was associated with reduced 30 day MACE (3.2% vs 9.5%); adjusted HR 0.53 (0.38–0.73)); mortality (1.8% vs 6.6%; adjusted HR 0.51 (0.34–0.77)) and major bleeding (2.5% vs 9.0%; adjusted HR 0.52 (0.36–0.75)) compared to transfemoral (n=992; 29.3%) PPCI. Conclusion: In this large consecutive real-world series, transradial PPCI was associated with lower probability of major bleeding, MACE and mortality at 30 days compared to transfemoral PPCI after multivariable analysis.